PROBLEM ASPECTS AND DIRECTIONS OF THE DEVELOPMENT OF INTERMUNICIPAL COOPERATION OF COMMUNITIES IN THE SPHERE OF IMPROVING THE INFRASTRUCTURE OF SUPPORTING INNOVATIVE ACTIVITIES - SERDIUK, Olga (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The relevance of the development of inter-municipal cooperation of territorial communities of Ukraine in the sphere of ensuring stimulation of the spread of innovative activity as a key factor in strengthening the competitiveness of local economic and economic complexes has been revealed. The purpose of the study was to identify problematic aspects and substantiate proposals regarding directions and means of improving inter-municipal cooperation of communities in the field of improving the infrastructure to support innovative activities. Objective and subjective factors - characteristics of the deterioration of innovative activity parameters in Ukraine, which are also characteristic of the level of local self-government - have been determined. Systemic obstacles to the establishment and development of inter-municipal community cooperation in the field of infrastructure development supporting innovative activities and innovative business have been identified and characterized. A sequence of measures for the formation of inter-municipal community cooperation in the field of innovative infrastructure development has been developed, which involves the gradual completion of such stages as (1) diagnostic analysis of the endogenous and exogenous environment in order to determine promising market and innovation niches, where a technological breakthrough can give the best result, based on needs of economic and social development; (2) assessment of quantitative and qualitative characteristics of scientific, technological and innovative potential; (3) identification of strategic types of economic activity; (4) determination of competitive advantages and limitations of prospective development. The scientific novelty of the research results lies in the further development of the methodological foundations of cooperation between territorial communities in the field of economics. The applied value of the research results lies in the formation of the algorithm of actions of local self-government bodies on the way to the development of innovative infrastructure to support innovative business.